As mudanças institucionais ocorridas a partir do marco regulatório em uma empresa de saneamento - Loos, Kátia do Rocio Ihlenffeldt (2022)
The present research aims to verify the changes that occurred in a basic sanitation company, in the period from 2007 to 2020, after the regulatory framework of the sector. Therefore, a characterization of sanitation in the country will be made, presenting the evolution of the sector, the regulatory framework and the changes that occurred after the regulation of services. Regulation intermediates the relationship between society (consumers), the State (granting power) and the service provider. The exercise of regulation requires a system of laws, regulations, norms and policies that allow the intervention of the authority to simulate conditions of competition in public services of a monopoly nature, such as the provision of sanitation services. It is intended to demonstrate in this research how the quest to adapt to the regulatory framework has brought changes to the company, what are the difficulties encountered in operating in a regulated environment, what are the tools used to comply with the legislation, focusing on possible lines of action to aggregate more efficiency to this service. Therefore, this research takes place in a Sanitation Company located in the South of Brazil, here fictitiously called COSUSB, which has been operating in the market for more than 58 years, being a mixed capital company. Therefore, this dissertation raises the following question: What changes occurred in Companhia Sulista de Saneamento Basico (COSUSB), due to the regulatory framework of the basic sanitation sector in Brazil, in the period from 2007 to 2020? This is a qualitative research, classified as an exploratory-descriptive case study, in which interviews were used as the main source of data collection, as well as analysis of Company documents. The research project also seeks to demonstrate the current scenario of the regulation of basic sanitation services in Brazil, analyzing the new landmark of the sector that changed the regulation of sanitation in the country.